The Role of Invariant Natural Killer T Cells in Dendritic Cell Licensing, Cross-Priming, and Memory CD8+ T Cell Generation - Gottschalk, Catherine; Mettke, Elisabeth; Kurts, Christian (Frontiers in Immunology, 2015)
New vaccination strategies focus on achieving CD8+ T cell (CTL) immunity rather than on induction of protective antibody responses. While the requirement of CD4+ T (Th) cell help in dendritic cell (DC) activation and licensing, and in CTL memory induction has been described in several disease models, CTL responses may occur in a Th cell help independent manner. Natural Killer T cells (NKT cells) can substitute for Th cell help and license DC as well. NKT cells produce a broad spectrum of Th1 and Th2 cytokines, thereby inducing a similar set of costimulatory molecules and cytokines in DC. This form of licensing differs from Th cell help by inducing other chemokines: while Th cell licensed DC produce CCR5 ligands, NKT cell-licensed DC produce CCL17 which attracts CCR4+ CD8+ T cells for subsequent activation. It has recently been shown that iNKT cells do not only enhance immune responses against bacterial pathogens or parasites, but also play a role in viral infections. The inclusion of NKT cell ligands in Influenza virus vaccines enhanced memory CTL generation and protective immunity in a mouse model. This review will focus on the role of iNKT cells in the cross-talk with cross-priming DC and memory CD8+ T cell formation.